The effect of leader’s interpersonal communication skills on nurses innovative behaviour / Siti Asiah Md. Shahid ... [et al.] - Md. Shahid, Siti Asiah; Gumbri, Darma Tasiyah; Othman, Abdul Kadir; Harun, Shariff (Research Management Centre (RMC), 2021)
The aim of this study is to examine the relationship between leaders’ interpersonal communication skills and nurses’ innovative behaviour. Moreover, innovative behaviour is essential for nurses in today’s dynamic healthcare systems whereby, the interpersonal communication skill has become an increasingly important factor in enhancing innovative behaviour. This study is based on the conceptual framework of interpersonal communication skills, innovative behaviour, and perceived trustworthiness. Using stratified sampling technique, questionnaires were distributed to 246 nurses’ grade U29 in three public state hospitals in the northern region of Peninsular Malaysia. Since this is a correlational study, a quantitative research method is employed to determine the existing relationship between the variables. Findings indicated that the head nurses implemented moderately all the five components of interpersonal communication skills. The existence of perceived trustworthiness was found to improve the interaction between both parties to transform nurses to generate innovation in their work. The study concluded that interpersonal communication skills are required to be implemented by leaders in enhancing nurses’ innovative behaviour.